Disturbance of waterfowl by boaters on pool 4 of the Upper Mississippi River Fish and Wildlife Refuge - Rasmussen, Hallie (My University, 2007)
The Upper Mississippi National Wildlife and Fish Refuge is currently undergoing a Comprehensive Conservation Plan (CCP) that will determine how the river will be managed over the next 15 years. The research I have conducted focuses on Pool 4 of the Mississippi River, which is a popular resting and feeding site for waterfowl during migration. Data was collected at two specific sites on Pool 4. The first is Peterson Lake which is currently closed to waterfowl hunting. The second is Big Lake which is currently open to all hunting. Part of the CCP proposes to close Big Lake in 2009 to waterfowl hunting and incorporate boating corridors to better protect the waterfowl that use the area as a resting and feeding site. Big Lake experienced a much greater amount of disturbances during the observation period than Peterson Lake, and the majority of those disturbances were caused by hunting boats. Each time waterfowl were disturbed, they were forced to expend a certain amount of energy which they need to complete a successful migration. Overall, 293 boating incidents occurred on Big Lake during the observation period resulting in a total of 212 disturbances; whereas 58 boating incidents occurred on Peterson Lake resulting in a total of 23 disturbances.
Keywords: Upper Mississippi River National Wildlife and Fish Refuge; Boats and boating -- Mississippi River; Waterfowl -- Mississippi River